The Impact of Cloud Computing on the Growth of Technology Startups - Alfallah, Fadhly; Veri, Jhon (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This study focuses on the Impact of Cloud Computing on the Growth of Technology Startups. Using the Systematic Literature Review (SLR) approach, this study analyzed 95 articles from various academic sources such as Google Scholar. The collected data was extracted using tools such as Publish or Perish. to filter articles relevant to this topic. The results of the study indicate that the adoption of cloud computing provides the flexibility and scalability that are much needed by startups to face market dynamics. In addition, cloud-based services enable better collaboration and accelerate product time-to-market. This study highlights the importance of an effective cloud computing implementation strategy to maximize its positive impact on the growth of technology startups.